On the Generalized Ulam-Hyers-Rassias Stability of Quadratic Mappings in Modular Spaces without Δ2-Conditions - Kittipong Wongkum; Parin Chaipunya; Poom Kumam (Journal of Function Spaces)
We approach the generalized Ulam-Hyers-Rassias (briefly, UHR) stability of quadratic functional equations via the extensive studies of fixed point theory. Our results are obtained in the framework of modular spaces whose modulars are lower semicontinuous (briefly, lsc) but do not satisfy any relatives of Δ2-conditions.